Use of Electronic Cigarette or Vape Associated with Massive Hemoptysis: Case Report - Valerio, María Gabriela Pesqueira; Martínez, Jonhy Robles; Carrillo, Gerardo Garza; Trinidad, Sergio Alberto López; Moreno, Miguel Angel Valencia (British Journal of Healthcare and Medical Research, 2024)
Vaping involves the use of a device to deliver aerosolized substances to the lungs, its popularity continues to increase; However, because it is a new drug delivery system, there is little evidence about its safety and long-term use. We present the case of a 37-year-old man, with a history of vaping with cannabis oil and tetrahydrocannabinol (THC), who presented with a hemoptoic cough. A diagnosis of lung injury associated with electronic cigarettes or vaping (EVALI) is made, visible by chest CT, as well as by angiotomography of the pulmonary arteries. The patient developed massive hemoptysis and hypovolemic shock, which made it necessary to perform a right lower lobectomy. There are reports in the literature associated with this case, however, no one was found that associated it with massive hemoptysis and/or the need to perform lobectomy.